RENCANA PENGEMBANGAN SEKOLAH - Mirzan Mirzan; Zakaria Zakaria (UNIVERSITAS BENGKULU, 2020)
This study described the school development plan in senior high school Number 2 Kepahiang. In the study used a qualitative descriptive method. While the subjects of this study were the principal, vice principal, teachers, administrative staff, parents of students, and students. In collecting data, the method used by the researcher is interview, observation, and documentation. then, the data collected will be analyzed using qualitative descriptive techniques such as those proposed by Miles and Huberman. The results of this study indicate that in general the plans for developing schools in Kepahiang 2 Public High School have not met the standard operating procedures that have been set.